Investigation of mineralization in copper-porphyry molybdenum using hydrothermal alternation in northwest region of Iran - Seddighi Takrami, Masumeh; Ganji, Alireza; Gorabjiripor, Arash; Ansari, Mohammadreza; Ashjaardalan, Afshin (Nexo Revista Científica, 2020)
Identification and determination of areas with mineral potential is one of the major and important applications of remote sensing in the field of mineral exploration. The aim of the present study was Identification of hydrothermal ultrason region using Landsat multispectral satellite imagery and hyperion hyperspectral imagery. To conduct this research, first the Advanced Space Borne thermal reflection radiometric data and the base metal mapping of the harvest were examined. Using principal component analysis using the key spectral change properties of key minerals, PC 2 enhanced the altered regions. Then we studied the MF spectral library and laboratory spectra of samples in the study area. In this study, two different methods, principal component analysis (PCA) and matched filter processing (MF), were compared and combined for mapping. In both methods, the key properties of changing the range of minerals in the study area were used. The results of the present study showed that from the top of the deposit to the bottom, the type of mineralization is gradually increasing. Chalcopyrite spraying gradually decreases from the depth of the deposit to the outer regions and vice versa, the amount of pyrite spraying increases. In Sungun, the main mineralization of copper in the second (main) stage of the activity of mineralized solutions has taken place, during which chalcopyrite has been extensively left in the form of vessels and sprays in rocks. Molybdenite is formed in a wide range of second stage mineralization processes in several successive phases. In the early processes, this mineral is sprayed and less in the form of veins and in later stages more in the form of veins. Thus, the copper-molybdenum porphyry deposit of Sungun Ahar, with a very high reserve of 7.1 billion tons and an average copper grade of 0.75 ٪ And molybdenite by-mineral in the early 80's will certainly be exploited among the largest copper mines in Iran.